2001
DOI: 10.1002/hed.1047
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative risk assessment for gastrostomy tube placement in head and neck cancer patients

Abstract: High-risk patients based on these criteria should receive a feeding gastrostomy at the time of their initial surgical therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
1
3

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 24 publications
3
27
1
3
Order By: Relevance
“…The results of this work are in keeping with those of earlier studies, which showed benefit from nutritional support in patients with head and neck cancer who were treated by surgery [8] and intensive radiation therapy [4,5,9]. In a preliminary study, Hearne et al [4] randomised 26 patients to receive either oral or tube feeding during radiotherapy.…”
Section: Discussionsupporting
confidence: 84%
“…The results of this work are in keeping with those of earlier studies, which showed benefit from nutritional support in patients with head and neck cancer who were treated by surgery [8] and intensive radiation therapy [4,5,9]. In a preliminary study, Hearne et al [4] randomised 26 patients to receive either oral or tube feeding during radiotherapy.…”
Section: Discussionsupporting
confidence: 84%
“…A gastrostomy at the time of initial surgical therapy was recommended in this subset of patients. 23 An argument against PEG has been the anecdotal observations of prolonged PEG dependence and increased need for pharyngoesophageal dilatation for persistent dysphagia. 24 Pretreatment swallowing exercises produces measurable improvements in post-treatment swallowing function in patients who undergo organ-preservation chemoradiation (CT/RT) for head and neck cancer and might reduce dependence on PEG.…”
Section: Head and Neck Cancer-clinical Considerationsmentioning
confidence: 99%
“…Groups have identified some factors that are predictive of a need for enteral support. 3,4,[14][15][16][17] One factor that has been clearly established is radiation therapy, particular when given postoperatively. 3,4,17 Other factors such as Stage IV disease, base of tongue tumor location, and heavy alcohol ingestion are less clearly defined.…”
Section: Introductionmentioning
confidence: 99%
“…3,4,17 Other factors such as Stage IV disease, base of tongue tumor location, and heavy alcohol ingestion are less clearly defined. [14][15][16] Some criticisms have been that the studies conducted to identify these variables were small, used a mixed population of surgical and non-surgical patients, and often used durations of enteral support that were short (< 4 weeks) or undefined. At Roswell Park Cancer Institute (RPCI) prophylactic PEG are routinely placed in surgically treated patients who require a composite resection, flap reconstruction, radiation therapy, chemotherapy, and at the discretion of the attending surgical staff.…”
Section: Introductionmentioning
confidence: 99%